(394) Formulation of Some Optimization Problems in Queuing Theory صياغة بعض مسائل التحسين في نظرية صفوف الانتظار - Saaty, T. L. (معهد التخطيط القومى, 2024)
This study explores queueing theory as a branch of probability widely applied in operations research. While traditionally descriptive, this research aims to introduce a "normative" optimization framework for queueing theory. The focus is on optimization problems, such as determining the service distribution that minimizes the expected waiting time under certain input distribution assumptions. Additionally, it investigates how to reduce expected idle time in a service channel by fixing the service distribution and varying the input distribution. Another objective is finding optimal combinations of input and service distributions to minimize expected waiting time. The study highlights that these problems have not yet been extensively addressed.